Position, Navigation, and Timing (PNT) Through Low Earth Orbit (LEO) Satellites : A Survey on Current Status, Challenges, and Opportunities - Prol, F. S.; Morales Ferre, R.; Saleem, Z.; Välisuo, P.; Pinell, C.; Lohan, E. S.; Elsanhoury, M.; Elmusrati, M.; Islam, S.; Çelikbilek, K.; Selvan, K.; Yliaho, J.; et al. (IEEE, 2022)
More and more satellites are populating the sky nowadays in the Low Earth orbits (LEO). Most of the targeted applications are related to broadband and narrowband communications, Earth observation, synthetic aperture radar, and internet-of-Things (IoT) connectivity. In addition to these targeted applications, there is yet-to-be-harnessed potential for LEO and positioning, navigation, and timing (PNT) systems, or what is nowadays referred to as LEO-PNT. No commercial LEO-PNT solutions currently exist and there is no unified research on LEO-PNT concepts. Our survey aims to fill the gaps in knowledge regarding what a LEO-PNT system entails, its technical design steps and challenges, what physical layer parameters are viable solutions, what tools can be used for a LEO-PNT design (e.g., optimisation steps, hardware and software simulators, etc.), the existing models of wireless channels for satellite-to-ground and ground-to-satellite propagation, and the commercial prospects of a future LEO-PNT system. A comprehensive and multidisciplinary survey is provided by a team of authors with complementary expertise in wireless communications, signal processing, navigation and tracking, physics, machine learning, Earth observation, remote sensing, digital economy, and business models.
Keywords: Constellation design; LEO business models; low earth orbit positioning; navigation and timing; receiver optimisation; satellite-to-ground channel models; fi=Automaatiotekniikka|en=Automation Technology|